Manajemen Bahasa Penulisan Proposal Mahasiswa Nonkebahasaan - Widyatmike Gede Mulawarman; Nanda Noviyanti (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This research raised the issue of language management as (1) the planning process in determining the vision and mission of writing a proposal (formulating a topic), (2) organizing (compiling the proposal writing structure as effectively as possible), (3) conducting a leadership strategy, that is, a strategy related to motivating, influencing and directing the reader, and (4) controlling (editing or editing the proposal writing). These four aspects of language management are focused on the use of Indonesian in proposals in terms of (1) sentence structure, (2) structure, (3) meaning/diction, and (4) writing. The subject of this study was a student proposal from the Faculty of Economics, Mulawarman University. Data in the form of language management, namely the planning process of writing proposals to editing student proposals is collected by the documentation method. To strengthen the classification of variations in language use on proposals, validation is carried out from experts in the field of error analysis or in the field of applied linguistics. Data in the form of eleven proposals from the Faculty of Economics students were analyzed using descriptive analysis methods. The results showed that in the proposal writing of non-linguistic students had fulfilled the four aspects of language management (style of environment of the faculty of economics) namely, the stages of planning, organizing, writing, and editing. In addition to paying attention to writing management, writing a proposal also has writing characteristics. Krakteristik is the hallmark of an idea both in writing and presentation. Characteristics contain facts, contain both title and problem descriptions, use of theory, problem-solving and conclude. found a variety of deviations in the use of language, both relating to the sentence structure, the formations, the order of meaning/diction, and writing.